Remarkable recent changes in the genetic diversity of the avirulence gene AvrStb6 in global populations of the wheat pathogen Zymoseptoria tritici. (14th July 2021) - Stephens, Christopher; Ölmez, Fatih; Blyth, Hannah; McDonald, Megan; Bansal, Anuradha; Turgay, Emine Burcu; Hahn, Florian; Saintenac, Cyrille; Nekrasov, Vladimir; Solomon, Peter; Milgate, Andrew; Fraaije, Bart; et al.
Abstract: Septoria tritici blotch (STB), caused by the fungus Zymoseptoria tritici, is one of the most economically important diseases of wheat. Recently, both factors of a gene‐for‐gene interaction between Z . tritici and wheat, the wheat receptor‐like kinase Stb6 and the Z . tritici secreted effector protein AvrStb6, have been identified. Previous analyses revealed a high diversity of AvrStb6 haplotypes present in earlier Z . tritici isolate collections, with up to c.18% of analysed isolates possessing the avirulence isoform of AvrStb6 identical to that originally identified in the reference isolate IPO323. With Stb6 present in many commercial wheat cultivars globally, we aimed to assess potential changes in AvrStb6 genetic diversity and the incidence of haplotypes allowing evasion of Stb6 ‐mediated resistance in more recent Z . tritici populations. Here we show, using targeted resequencing of AvrStb6, that this gene is universally present in field isolates sampled from major wheat‐growing regions of the world in 2013–2017. However, in contrast to the data from previous AvrStb6 population studies, we report a complete absence of the originally described avirulence isoform of AvrStb6 amongst modern Z . tritici isolates. Moreover, a remarkably small number of haplotypes, each encoding AvrStb6 protein isoforms conditioning virulence on Stb6‐ containing wheat, were found to predominate among modern Z . tritici isolates. A single virulence isoform of AvrStb6 was found to be particularly abundant throughout the global population. These findings indicate that, despite the ability of Z . tritici to sexually reproduce on resistant hosts, AvrStb6 avirulence haplotypes tend to be eliminated in subsequent populations. Abstract : A snapshot of AvrStb6 isoforms diversity amongst earlier versus more recent natural Zymoseptoria tritici populations revealed a marked decrease in diversity and a global shift to virulence on Stb6 wheat.